Potential and limitations of Klebsiella pneumoniae as a microbial cell factory utilizing glycerol as the carbon source - Kumar, Vinod; Park, Sunghoon (Elsevier, 2017)
Klebsiella pneumoniae is a Gram-negative facultative anaerobe that metabolizes glycerol efficiently under both aerobic and anaerobic conditions. This microbe is considered an outstanding biocatalyst for transforming glycerol into a variety of value-added products. Crude glycerol is a cheap carbon source and can be converted by K. pneumoniae into useful compounds such as lactic acid, 3-hydroxypropionic acid, ethanol, 1,3-propanediol, 2,3-butanediol, and succinic acid. This review summarizes glycerol metabolism in K. pneumoniae and its potential as a microbial cell factory for the production of commercially important acids and alcohols. Although many challenges remain, K. pneumoniae is a promising workhorse when glycerol is used as the carbon source.
Keywords: Klebsiella pneumoniae; Glycerol; 3-Hydroxypropionic acid; 1,3-Propanediol; 2,3-Butanediol; Lactic acid; Ethanol